Human Ecology and Adaptive Governance in Vulnerable Mangrove Ecosystems: Global Trends and Implications for Indonesia - Riesti Triyanti; Tri Retnaningsih Soeprobowati; Sri Sumiyati; Nur Arifatul Ulya (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2026)
Mangrove  ecosystems  are  vital  for  coastal  socio-ecological  resilience,  yet  governance  outcomes  often  remain weak  due  to  institutional  fragmentation  and  escalating  climate  risks.  This  study  combines  a  PRISMA  2020 systematic review with bibliometric mapping (VOSviewer) of 520 Scopus-indexed publications (2000–2025) to trace global research evolution and derive Indonesia-relevant insights. Publication output accelerated sharply after 2018, peaking at >60 documents in 2024, and research production is concentrated in high-income countries (e.g., the United States ~18.6%), while Indonesia contributes only ~9.7% despite hosting the world’s largest mangrove extent. Keyword mapping identifies three dominant clusters—ecological foundations, human ecology and  governance,  and  environmental  dynamics—with  recent  trends  shifting  toward  climate–governance  and resilience themes. The key gap is that governance and resilience discourse rarely translates into an integrated institutional design linking multi-level coordination, community adaptive capacity, and long-term financing; the novelty of this study is the Dynamic Adaptive Institutional Alignment Framework that explicitly integrates these components to inform Indonesia-oriented governance reform. Findings support moving beyond restoration targets toward adaptive, learning-based, and financially durable governance architectures. The study contributes theoretically by operationalizing adaptive governance within mangrove socio-ecological systems and offers policy guidance for strengthening climate-responsive and inclusive coastal governance under conditions of increasing uncertainty.